1991
DOI: 10.1093/bja/66.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Extradural and Intrathecal Sufentanil Anaesthesia for Major Surgery

Abstract: We have studied the plasma concentrations (Cp) and pharmacokinetics of sufentanil injected i.v. (IVS), intradurally (IS) or extradurally (ES) under general anaesthesia in 31 patients undergoing major abdominal surgery. Sufentanil appeared in plasma very rapidly and Cpmax was also attained rapidly after both extradural and intrathecal injection. Apart from the first 2 min after injection, Cp after ES and IVS were comparable until the end of the study. Cp after ES was greater than after IS up to 0.25 h. Cp after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 0 publications
1
13
0
3
Order By: Relevance
“…In contrast, Hansdottir et al 15 stated that after an IT injection in humans, sufentanil is rapidly cleared from cerebrospinal fluid and absorbed by plasma, with a mean residence time much longer in plasma (7 hours) than in cerebrospinal fluid (1 hour). Ionescu et al, 16 who compared only plasma concentrations after IT or IV administration of 150 g sufentanil, described a statistically similar plasma concentration in both groups at 30 minutes, whereas the peak plasma sufentanil concentration after IT injection was at 15 minutes. These findings support a supraspinal effect by systemic uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Hansdottir et al 15 stated that after an IT injection in humans, sufentanil is rapidly cleared from cerebrospinal fluid and absorbed by plasma, with a mean residence time much longer in plasma (7 hours) than in cerebrospinal fluid (1 hour). Ionescu et al, 16 who compared only plasma concentrations after IT or IV administration of 150 g sufentanil, described a statistically similar plasma concentration in both groups at 30 minutes, whereas the peak plasma sufentanil concentration after IT injection was at 15 minutes. These findings support a supraspinal effect by systemic uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators were unable to demonstrate any difference in pain scores when the same dose of sufentanil was given either intravenously or epidurally. 8,21 These findings have led some clinicians to question the concept of a spinal cord effect with lipid soluble epidural opioids, and suggest that any improvement in analgesia is secondary to systemic uptake. To distinguish between systemic effect and direct spread in CSF, and any impact the addition of epinephrine has on systemic levels, plasma sufentanil levels would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil has been evaluated in combination with local anesthetics in the epidural 1,2 and intrathecal space. 1,3,4 As a sole epidural agent, its use is less prevalent but studies have evaluated its analgesic effectiveness and pharmacokinetics in the obstetric 2,5,6 and non-obstetric 7,8 populations. Dunn et al concluded that 40 µg of sufentanil administered epidurally, after a test dose of lidocaine and epinephrine, is as effective as 10 µg of intrathecal sufentanil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, procedimentos hospitalares para o paciente cirúrgico, como a circulação extracorpórea (CEC) podem alterar a farmacocinética do analgésico opióide em questão devido a modificações na concentração de proteínas plasmáticas (alfa-1 glicoproteína ácida), pressão arterial, temperatura corpórea e equilíbrio ácido-base sanguíneo (SCHOLZ et al, 1996). IONESCU et al, 1991;CROSS et al, 1994;GEPTS et al, 1995;THOMSON et al, 1998;SCHRAAG et al, 1998;AHONEN et al, 2000;BARVAIS et al, 2000;HUDSON et al, 2001;ZHAO et al, 2009 …”
Section: Farmacocinética E Farmacodinâmicaunclassified